2019
DOI: 10.1111/jfpp.13896
|View full text |Cite
|
Sign up to set email alerts
|

Effect of location on some physico‐chemical properties of prickly pear (Opuntia ficus‐indicaL.) fruit and seeds

Abstract: Total phenolics, β‐carotene, and ascorbic acid contents of cactus fruits varied between 490.74 and 932.87 mg/100 g, 40.93 and 130.76 µg/kg, and 124.82 and 240.25 mg/kg, respectively. K and Ca values of prickly pear fruits changed between 1,908.10 and 3,981.90 mg/kg, and 136.79 and 1,224 mg/kg, respectively. Amounts of gallic acid, 3,4‐dihydroxybenzoic acid, catechin, 1,2‐dihydroxybenzene, syringic acid contents of prickly pear fruit pulps ranged from 0.86 to 166.02 mg/kg, 2.17 to 4.75 mg/kg, 3.29 to 15.55 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 32 publications
3
11
1
Order By: Relevance
“…It observed from the same table some differences between all compounds which may be due to growing conditions during two seasons. These findings are in agreement with Gissler and Powers (2010) and Belviranl et al (2019). From the previous results clearly evident that prickly pear is a good source in minerals and active compounds which work as antioxidants.…”
Section: Active Compoundssupporting
confidence: 91%
“…It observed from the same table some differences between all compounds which may be due to growing conditions during two seasons. These findings are in agreement with Gissler and Powers (2010) and Belviranl et al (2019). From the previous results clearly evident that prickly pear is a good source in minerals and active compounds which work as antioxidants.…”
Section: Active Compoundssupporting
confidence: 91%
“…1) [31]. The difference in the quality and quantity of fatty acids in O. dillenii and O. ficus-indica oils is generally linked to the climate and the geographical area that these two plants come from [32]. Moreover, the fatty acid composition of cactus grown in different places is significantly different.…”
Section: Fatty Acidsmentioning
confidence: 99%
“…On the other hand, the oils from the different regions showed no significant variation for oleic, palmitoleic and gadoleic acid. The effect fruit growing region on seed oil fatty acid composition was also evaluated on prickly pear grown in different locations in Turkey ( Belviranli et al., 2018 ). It was observed that the oils from Fethiye, Anamur and Iskenderun had the highest content of linoleic acid (63.38 %), oleic acid (15.46 %) and palmitic acid (11.777 %), respectively.…”
Section: Preharvest Factors Affecting Quality Attributes Of Edible Frmentioning
confidence: 99%
“…(2017) Papaya Air drying (room temperature), freeze drying (72 h), oven drying (50 °C, 48 h), sun drying (3 days) Oil extracts from freeze dried seeds showed higher TEAC (56.54 μMTE/g) and FRAP (150.01 μg GAE/g) Irondi et al. (2013) Microwave vacuum drying (100 mbar, 100, 300, 450 and 600 W) Microwave drying papaya seeds at 600 W produced oil with higher TEAC (0.15 mg TE/g DW) Bualuang et al. (2018) Kinnow mandarin, eureka lemon and orlendo orange Oven drying (60, 70 and 80 °C for 24 h).…”
Section: Processing Factors Affecting Quality Attributes Of Edible Frmentioning
confidence: 99%